A2.36 Dynamics of T-cell subset in early ra patients treated with mtx or MTX+ANTI-TNF. (24th February 2016) - Wigston, Z; Buch, MH; Burska, A; Emery, P; Ponchel, F
Abstract : Introduction: It has been recently established that the quantification of naïve CD4 + T-cell frequency at baseline can predict the outcome of MTX treatment (1). The purpose of this study was to investigate whether T-cell subsets varied during treatment with MTX and MTX+anti-TNF. Methods: Fresh blood samples were collected from 116 patients with early RA that had received no previous DMARDs: a first group received MTX (n = 67) and the second MTX+anti-TNF (n = 49). Flow cytometry was conducted at 3 monthly intervals using standard protocols. The frequency of naïve and IRC subsets were recorded as% of CD4 + T-cells. Naïve T-cells decrease with age but IRC are more closely related to levels of inflammation (2). The deviation from the expected age-corrected frequency was calculated for naïve cells and used to analyse data. Results: At baseline, there was no difference in the average frequency of naive CD4 + T-cells and IRC between treatment groups. The average frequency of naïve CD4 + T-cells increased slowly from week 26 to week 48 in the MTX group plateaued at ˜2.8 fold. In contrast, in the MTX+anti-TNF group, naïve cell frequency increases steadily from baseline up to 6.5 fold at 48 weeks. IRC marginally increased in the MTX group (1.25 fold at week 48) but were immediately reduced by half (0.46 fold) in the MTX+anti-TNF group and stayed low up to week 48 (p < 0.001 at all time-points). Conclusion: Results suggest an association between better inflammation control resulting in lower IRC frequency in the MTX+anti-TNF group as well as a steady increase in naïve cells frequency observed with more aggressive treatment. Considering the predictive value of naïve cell frequency at baseline (1), continued naive cells deterioration in the MTX group is an important finding suggesting lack of immune function recovery compare to the MTX+anti-TNF. References: F Ponchel, et al . ARD. 2014;73:2047-2053 F Ponchel, et al. Blood. 2002;100:4550–4556